Biological activity and chemical composition of native fruits: a review - Elisa dos Santos Pereira; Chirle de Oliveira Raphaelli; Marjana Radünz; Taiane Mota Camargo; Márcia Vizzotto (Agrociencia Uruguay, 2022)
Brazilian native fruit trees have great potential for their use in the food and pharmaceutical industries. Among these, the Myrtaceae family stand out for the diversity of known native fruits, as the case of “araçazeiro” or cattley guava [Psidium cattleianum], “pitangueira”, Suriname cherry or Brazilian cherry [Eugenia uniflora], “guabijuzeiro” [Myrcianthes pungens], “guabirobeira” [Campomanesia xanthocarpa] and “uvalheira” [Eugenia pyriformis]. These fruits contain substances of nutritional and potentially functional importance, including dietary fiber, vitamins (especially A and C) and minerals (potassium, iron, manganese, magnesium, calcium, phosphorus), as well as antioxidant compounds, such as phenolics and carotenoids. The consumption of fruits rich in bioactive compounds and high antioxidant activity has the potential to prevent chronic non-communicable diseases such as cancer, diabetes mellitus, dyslipidemias, cardiovascular diseases, and chronic respiratory diseases. For example, Suriname cherry and cattley guava fruit extracts showed anti-hyperglycemic, antidyslipidemic and antioxidant effects in animal models with insulin resistance, cattley guava also showed anticarcinogenic, antimicrobial, anti-inflammatory and anti-aging activities. “Uvaia” has a promising effect as an antimicrobial agent. In this review, summarized information on the main native fruits of the Myrtaceae is presented, highlighting their composition and biological activities in order to direct new research.